2021
DOI: 10.1038/s41467-021-23546-6
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-modified VEGFC mRNA induces organ-specific lymphatic growth and reverses experimental lymphedema

Abstract: Lack or dysfunction of the lymphatics leads to secondary lymphedema formation that seriously reduces the function of the affected organs and results in degradation of quality of life. Currently, there is no definitive treatment option for lymphedema. Here, we utilized nucleoside-modified mRNA encapsulated in lipid nanoparticles (LNPs) encoding murine Vascular Endothelial Growth Factor C (VEGFC) to stimulate lymphatic growth and function and reduce experimental lymphedema in mouse models. We demonstrated that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 63 publications
(114 reference statements)
0
20
0
2
Order By: Relevance
“…After intraperitoneal injection, increased lymphatic growth was detected in the diaphragm; after intratracheal injection, in the lungs; and after intramuscular administration, in the musculus gastrocnemius. 61 A second line of evidence also suggests that the mRNA drug kinetics change with the route of administration. In mice, intramuscular delivery increased the half-life of mRNA translation nearly 3-fold, from 6.8 h after systemic administration to 20.6 h after intramuscular administration.…”
Section: Lymphatic Deliverymentioning
confidence: 99%
“…After intraperitoneal injection, increased lymphatic growth was detected in the diaphragm; after intratracheal injection, in the lungs; and after intramuscular administration, in the musculus gastrocnemius. 61 A second line of evidence also suggests that the mRNA drug kinetics change with the route of administration. In mice, intramuscular delivery increased the half-life of mRNA translation nearly 3-fold, from 6.8 h after systemic administration to 20.6 h after intramuscular administration.…”
Section: Lymphatic Deliverymentioning
confidence: 99%
“…(Brown et al, 2020) Szoke et al recently reported on the use of nucleoside modified VEGF-C mRNA delivered using lipid nanoparticles to promote organ-specific lymphangiogenesis and treat experimentally induced lymphedema. (Szőke et al, 2021) They showed that injection of the VEGF lipid nanoparticles increased VEGF-C expression locally for as long as 20 days after treatment. This increased VEGF-C production significantly increased lymphangiogenesis that persisted even 60 days after injection.…”
Section: Vascular Endothelial Growth Factorsmentioning
confidence: 99%
“…A single low-dose administration of VEGF-C mRNA-LNPs induced organ-specific lymphatic growth in mice. Most important, treatment with VEGF-C mRNA-LNPs was able to reverse lymphedema and restore lymphatic function in an experimental lymphedema mouse model (Szőke et al 2021).…”
Section: Directly Applied Into Defect Areamentioning
confidence: 99%